2013
DOI: 10.1007/s00381-013-2111-y
|View full text |Cite
|
Sign up to set email alerts
|

Congenital hydrocephalus in the northeast of Brazil: epidemiological aspects, prenatal diagnosis, and treatment

Abstract: Public health measures are the key to increase mothers' knowledge about the importance of regular prenatal monitoring. There was a predominance of male children, with a median age of 3 months, with the majority coming from the countryside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…Our data corroborate these earlier findings; the patients treated with a VP shunt for initial PHH management had higher complication rates than those treated with a VP shunt as a second option during the follow-up period. In a series of children with congenital hydrocephalus described previously by our team 24 , we observed a much lower incidence of VP shunt-related complications than those observed in the current series, which confirms the need for extreme care in the selection of PHH patients for a VP shunt as a first CSF drainage option.…”
Section: Discussionsupporting
confidence: 87%
“…Our data corroborate these earlier findings; the patients treated with a VP shunt for initial PHH management had higher complication rates than those treated with a VP shunt as a second option during the follow-up period. In a series of children with congenital hydrocephalus described previously by our team 24 , we observed a much lower incidence of VP shunt-related complications than those observed in the current series, which confirms the need for extreme care in the selection of PHH patients for a VP shunt as a first CSF drainage option.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study identified the irregularity and deficiency of prenatal monitoring in pregnant women, assisted by a poor public health system, in the state of Bahia (Brazil) 17 and indicated that these may be associated with the high incidence of spinal dysraphism 5,22,23 . We recommend, as suggested by other authors, that at least 400 µg of a folic acid supplement should be consumed daily; patients with an intermediate to high risk of neural tube defects (such as patients with a previous well-known history of neural tube defects) should consume 4-5 mg folic acid 5,22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…We consider the measure of HC and evaluation of the fontanels as the most important clinical signs to be observed in these children, according to previously published studies 11,15,16,17,19 . Infant girls with HC of 37.7 cm and infant boys with HC of 38.5 cm who showed an increase in the ventricular system were considered as having hydrocephalus since birth 17,18,20 . In this group, the proposal for treatment was of closure of MM and VP shunt at the same surgical time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations